The Opinions the Towards Evaulation Performances of Instructors of Primary Teacher Candidates - Serhat Süral (International Journal of Assessment Tools in Education)
Evaluating the performance of teachers by teaching staff in faculties of education were asked. To sum up, the instructor of the class teacher education courses within the program, course performance, it is intended that teachers have taken the course evaluation by the instructor. General screening model is used in the conduct of the trial, was designed with a descriptive survey method. the class teachers constitute 117 teachers. In order to evaluate the performance of teaching staff Diver (2010) "developed by Teacher Performance Assessment" is used inventory. Despite teacher candidates applied to the inventory offered as an option to evaluate all training courses, training courses they take in life science teaching evaluation, teaching social studies, science and technology education and mathematics education courses.